Increasing Knowledge of Bali Cattle Farmers Through Counseling and Technical Guidance in Palangga District, South Konawe - Eka Fitriani; La Ode Nafiu; La Ode Arsad Sani (Pascasarjana Universitas Sulawesi Tenggara, 2023)
This study aims to analyze (1) the implementation of extension activities and technical guidance and (2) the increased knowledge of cattle farmers in extension activities and technical guidance in Palangga District. The model used in this activity is delivering material through counseling and technical guidance. The results of the research obtained are at the stage of conducting research carried out by delivering material directly with the discussion method followed by field activities, namely technical guidance, and to measure the increase in knowledge and skills of farmers with counseling and technical guidance, a pre-test evaluation is carried out and continued with post-test evaluation. Then, based on the results of the recapitulation of pre-test and post-test data analysis, it showed an increase in the knowledge and skills of related farmers: (a) management of maintenance and selection of Bali cattle breeds increased by 30%, (b) forage and animal feed management by 61%, (c) control and prevention of mouth and hoof disease (FMD) by 43%, and (d) post-harvest management by 26%.